2018
DOI: 10.18240/ijo.2018.07.09
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol delamination of the corneal epithelium for recurrent corneal erosion syndrome

Abstract: ALD is an efficacious and cost-effective primary surgical intervention for RCES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A clinical audit reported that alcohol delamination meets the typical safety and efficacy standards. 11 In our case series, alcohol-assisted epithelial debridement was effective and safe in the treatment of RCE. All our patients had complete resolution within 2 weeks and had no recurrence after a mean follow-up period of 27 months.…”
Section: Discussionmentioning
confidence: 56%
“…A clinical audit reported that alcohol delamination meets the typical safety and efficacy standards. 11 In our case series, alcohol-assisted epithelial debridement was effective and safe in the treatment of RCE. All our patients had complete resolution within 2 weeks and had no recurrence after a mean follow-up period of 27 months.…”
Section: Discussionmentioning
confidence: 56%
“…Medical treatments include lubricating ointments, hypertonic NaCl drops and hypertonic ointments [ 4 ]. Erythromycin or tetracycline ophthalmic ointments can reduce matrix metalloproteinase-9, which could contribute to the recurrent erosions [ 32 ]. Collagen shields and bandage contact lenses (BCL) [ 33 ] have also been used for recurrent erosions, but it is preferable not to use BCL for an extended period because of the potential problem of bacterial ulceration.…”
Section: Discussionmentioning
confidence: 99%